How do nurses and midwives perceive their role in sexual healthcare? - Mathilde Azar; Thilo Kroll; Caroline Bradbury-Jones (BMC Women's Health, 2022)
Abstract Background Nurses and midwives role in sexual healthcare is essential to help patients, particularly women, ensure a satisfactory sexual wellbeing. Yet, these professionals often overlook this aspect of patients’ health. Little is known regarding nurses and midwives’ attitudes, views and experiences concerning sexual healthcare. Using a naturalistic inquiry approach, this qualitative study was conducted to overcome this limitation and gain insights into nurses and midwives' role in the delivery of sexual healthcare. Methods A purposive sample of nurses and midwives was chosen from different clinical sites. Data generated by focus group discussions were were analysed using the Framework Analysis while adopting different strategies to ensure rigour. The study aligns with the consolidated criteria for reporting qualitative research checklist. Results Five themes illustrated the participants’ views and experiences. These are: ‘Perceptions of sexuality’, ‘Appreciating the discussion around the individuals' sexual issues’, ‘Muting the discussion around the individuals’ sexual issues, ‘Coping with embarrassment’, and ‘Promoting nurses’ and midwives’ roles sexual healthcare’. Nurses and midwives discussed the importance of sexuality in the couple's life. They reported controversial views and highlighted many challenges that make them reluctant in playing an efficient role in sexual healthcare. They discussed many suggestions, mainly getting a solid sexual health education to become better equipped to meet patients’ sexual health needs. Conclusion Findings are critical to empower nurses and midwives, break the barriers in discussing sexual healthcare and integrate this aspects of care more actively and confidently in daily practice.